Study on Evaluation of Laparoscopic Retroperitoneal Approach for Management of Various Renal Calculi - Rudramani, .; Singh, Vikas; Kumar, Shesh; Kumar, Anil; Kumar, Shailendra; Singh, Manish Kr. (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
Background: Laparoscopic surgery as an alternate to open surgery has been grown in recent years as a result of the increasing use of laparoscopy in urology together with inherent limitations of Percutaneous nephrolithotomy (PCNL). Evaluation of Laparoscopic retroperitoneal approach for management of various renal calculi must be done to get the efficacy of the procedure according to the calculus and renal morphology. Aims: The aim of present study was to evaluate laparoscopic retroperitoneal approach for management of various renal calculi. Methods: Laparoscopic retroperitoneal pyelolithotomy/nephrolithotomy was performed on 58 patients with various renal calculi patterns viz. solitary pelvic calculus, staghorn calculus, staghorn calculus with calyceal and isolated calyceal calculi. Extended pyelolithotomy, Gilvernet’s technique were used as per the need. Results: Out of the 58 cases with renal calculi, solitary renal pelvic stones (n=23; 39.7%) were most common followed by staghorn (n=11; 19% Mean size 4.40±1.17 cm) and isolated caliceal stones (n=9; 15.5% with Mean size2.21±0.25 cm) respectively. There were 15 (25.9%) cases with mixed stones (11 cases solitary renal pelvic and isolated caliceal stones and 4 cases had staghorn and isolated caliceal stones). Stone clearance was 93.3 to 100%. Conclusions: laparoscopic retroperitoneal approach is a useful modality for clearance of renal calculi of different types with minimum complications and a high success rate. However, the technique seems to have a limited role for isolated caliceal stones where direct or C-arm guided nephrolithotomy can be performed for better clearance of stones.